1996
DOI: 10.1071/pp9960025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phosphoenolpyruvate Carboxylase in Zea mays by Protein Phosphorylation and Metabolites and Their Roles in Photosynthesis

Abstract: The effects of metabolites, protein phosphorylation and malate inhibition on phosphoenolpyruvate carboxylase (PEPC) activity were investigated at pH 7.0 in partially purified enzyme from maize leaves. Glycine, glucose 6-phosphate or alanine stimulated the activity two- to three-fold. Glycine and glucose 6-phosphate increased the affinity for PEP by factors of eight and four respectively. These metabolites changed the response of the enzyme activity to pH. Activity increased between pH 6.8 and 8.0 by 10-fold in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…This phosphorylation motif has previously been found in spruce by Relle and Wild (1996). Moreover, this phosphorylation state was reported to account for the modulation of some properties of the enzyme ( Duff et al 1995; Gao and Woo 1996). Particularly, phosphorylated PEPC was shown to be both more active and less sensitive to feedback inhibition by malate ( Nimmo et al 1987).…”
Section: Discussionsupporting
confidence: 69%
“…This phosphorylation motif has previously been found in spruce by Relle and Wild (1996). Moreover, this phosphorylation state was reported to account for the modulation of some properties of the enzyme ( Duff et al 1995; Gao and Woo 1996). Particularly, phosphorylated PEPC was shown to be both more active and less sensitive to feedback inhibition by malate ( Nimmo et al 1987).…”
Section: Discussionsupporting
confidence: 69%
“…Due to the reported regulatory interactions between malate and glycine it is noteworthy that R226Q and E229A are also desensitized to the activator glycine. Kinetic studies have shown that glycine can effectively overcome malate inhibition, raising the I 0.5 value for malate significantly (Gillinta and Grover 1995;Gao and Woo 1996;Tovar-Mendez et al 2000). Indeed, kinetic data suggest that glycine and malate bind in a mutually exclusive manner (Tovar-Mendez et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…The lysate was fractionated with 5-12% PEG-8000. The pellet was resuspended in buffer A for fast protein liquid chromatography (20 mM Tris, pH 8.0, 10% glycerol, 1 mM DTT, 0.1 mM EDTA) and purified on a Mono-Q column equilibrated with the buffer A [19,20]. The fractions (0.5 ml) containing high PEPC activity were pooled, desalted on a Sephadex-G-25 column and stored in 50% glycerol at -20°C.…”
Section: Partial Purification Of Pepcmentioning
confidence: 99%